Industrial Policy in an Imperfect World - Roland Hodler (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
Theoretical analyses of industrial policy normally restrict the range of possible outcomes by abstracting from either market or government failures. This paper thus studies industrial policy and its effectiveness in a model that includes both market and government imperfections. We introduce a public agency responsible for industrial policy into the model of Hausmann and Rodrik (2003), and assume that this agency has limited information and is partly politically motivated. We further extend the model to allow the public agency to communicate with en- trepreneurs and the entrepreneurs to engage in rent seeking. We find that industrial policies are ineffective if the public agency is poorly informed, but that they are not necessarily ineffective if the public agency is highly politically motivated. Given a highly politically mo- tivated public agency, industrial policies are effective if and only if the institutional setting ensures that such policies are modest e.g. by re- stricting the public agency?s budget. Moreover, our model helps us to understand why the same industrial policies that have failed elsewhere have been relatively successful in South Korea and Taiwan.
Keywords: O20; H25; L53; L52; 330; Industrial Policy; Market and Government Failures; Political Economy